Metabolno zdrava debelost - Jakše, Barbara (Šport (Ljubljana), 2017)
In the scientific and professional literature and among general public, we can find the potential existence of being overweight or clinically obese without the presence of the metabolic syndrome ("metabolically healthy obesity" or MHO). The potential existence of MHO is a much-examined hypothesis in the field of science, but is, at least on the level of the population, a repeatedly refuted paradox despite the occasional inconsistency of scientific data. Excessive body weight by itself presents a risk factor for chronic diseases, but when the metabolic syndrome is also present, the risk is significantly higher. There exist researches that suggest the opposite; that an individual can be overweight and without metabolic risk factors and still be healthy, especially if they are regularly physically active. This, seemingly benign condition, is most likely related with the inconsistent criteria of MHO and various methods of measuring obesity, making the topic even more controversial in public. There is also a growing percentage of increased fattiness with normal weight ("sarcopenic obesity" or SD), which also presents an increased risk to health. The aim of the article is to untangle the ambivalence of the obtained conclusions of different scientific researches on the topic of MHO and sarcopenic obesity and to do so through a relative overview of scientific literature.
Keywords: chronic diseases; exessive body weight; healthy obesity; kronične bolezni; metabolic syndrome; metabolni sindrom; MHO; MZD; prekomerna teža; sarcopenic obesity; sarkopenična debelost; SD; sport; šport; zdrava debelost